MENINGKATKAN PERLINDUNGAN INVESTOR DALAM USAHA HULU MINYAK DAN GAS BUMI DALAM KONTEKS INDONESIA - -, Mardianto; Pieris, John; Widiarty, Wiwik S. (Ilmu Hukum Prima (IHP), 2023)
The primary objective of this research is to assess the degree of legal assurance and protection accessible to investors involved in upstream oil and gas operations within the Republic of Indonesia's jurisdiction. The goal is to offer valuable insights to relevant decision-makers and stakeholders,  aiming to enhance the legal assurance and protection afforded to investors in this sector, thereby contributing to the nation's overall stability. The research methodology employed in this study is normative and qualitative juridical legal research, incorporating statutory and conceptual approaches. The research findings highlight the necessity for legislative enhancements, particularly implementing  the Job Creation Law. This legislation will  enhance the regulatory framework, ensuring legal assurance under Article 169, Section A of the Minerba Law. This provision stresses that holders of Mining Business Permits (KK) should not encounter premature contract terminations and advocates for rigorous law enforcement in cases of violations. Furthermore, the study acknowledges the significance of Law No. 25 of 2007, which safeguards legal and business assurance for investors, notably through the Omnibus Law.